2014
DOI: 10.1002/cam4.357
|View full text |Cite
|
Sign up to set email alerts
|

Setting up a wide panel of patient‐derived tumor xenografts of non–small cell lung cancer by improving the preanalytical steps

Abstract: With the ongoing need to improve therapy for non–small cell lung cancer (NSCLC) there has been increasing interest in developing reliable preclinical models to test novel therapeutics. Patient-derived tumor xenografts (PDX) are considered to be interesting candidates. However, the establishment of such model systems requires highly specialized research facilities and introduces logistic challenges. We aimed to establish an extensive well-characterized panel of NSCLC xenograft models in the context of a long-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 29 publications
7
56
1
Order By: Relevance
“…2,33 We also found that residual tumor tissue obtained from mice in which PDXs had not formed at ≥12 months after implantation of primary tumors often contained human CD8+ and/or CD20+ immune cells, indicating that the coimplantation of tumor-infiltrating immune cells with fresh tumor samples might be one of the factors preventing PDX growth in immunodeficient mice. Our analysis of PDX engraftment from surgically resected tumor specimens from 308 patients with NSCLC found an overall engraftment rate of approximately 35% in NSG mice.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…2,33 We also found that residual tumor tissue obtained from mice in which PDXs had not formed at ≥12 months after implantation of primary tumors often contained human CD8+ and/or CD20+ immune cells, indicating that the coimplantation of tumor-infiltrating immune cells with fresh tumor samples might be one of the factors preventing PDX growth in immunodeficient mice. Our analysis of PDX engraftment from surgically resected tumor specimens from 308 patients with NSCLC found an overall engraftment rate of approximately 35% in NSG mice.…”
Section: Discussionmentioning
confidence: 72%
“…2,33 The proliferation of EBV-positive B cells in tumor samples also has been reported to result in the formation of human B-cell lymphomas and the failure of PDX growth in specimens from patients with several types of cancer, including lung cancer. 2,33 The proliferation of EBV-positive B cells in tumor samples also has been reported to result in the formation of human B-cell lymphomas and the failure of PDX growth in specimens from patients with several types of cancer, including lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear to what extent they fully recapitulate the genetic, epigenetic, and signaling mechanisms that collectively drive clinical disease, especially for their matched patient tumors. At a broad level, PDXs harbor similar NSCLC profiles of gene copy number, mRNA and protein, and retain specific “driver” mutations of the matching primary tumors . Here, we now report the high concordance of genome‐wide exomic single nucleotide variants (SNVs) and gene copy number variants (CNVs) between 25 PDXs and their matched patient tumors, which comprehensively establishes the ability of PDXs to faithfully recapitulate the genetic mechanisms driving pathobiology of their specific corresponding patient tumors.…”
mentioning
confidence: 67%
“…Consequently, some cancers, such as neuroendocrine, luminal ER+ breast, and prostate cancers (Rosfjord et al, 2014) are underrepresented. Notably, PDX engraftibility appears to significantly correlate with clinical aggressiveness (Ilie et al, 2015 ).…”
Section: Mouse Cancer Models In Preclinical Researchmentioning
confidence: 99%